The utilization of technology in environmental education - Hamida Nurul Azizah (Curricula: Journal of Curriculum Development, 2024)
Environmental education is crucial for constructing public awareness regarding environmental issues and realizing Sustainable Development Goals (SDGs). Digital technology has enhanced connectivity between learners and the natural environment to create innovative digital learning tools. Therefore, the identified technology can be used to optimize the environmental education process. The methodology employed in this research is the literature review. The results demonstrated that augmented reality, virtual reality, the Internet of Things (IoT), and ICT (Information and Communication Technology) based technologies enhance learners' comprehension and engagement with environmental issues in their immediate surroundings. However, specific challenges to the utilization of technology were identified, including disparate technology infrastructure, a shortage of resources for training, and the high costs associated with implementation. This study can serve as a reference point for future research efforts aimed at addressing barriers and facilitating more productive integration of environmental education across educational contexts.   Abstrak Pendidikan lingkungan hidup penting untuk membangun kesadaran masyarakat terhadap isu-isu lingkungan dan mencapai tujuan pembangunan berkelanjutan (SDGs). Adanya teknologi digital telah mempermudah peserta didik terhubung dengan lingkungan dan menciptakan alat digital untuk pembelajaran. Sehingga identifikasi penggunaan teknologi penting untuk memaksimalkan proses pendidikan lingkungan. Metodologi yang digunakan dalam penelitian ini adalah studi pustaka. Hasil kajian menunjukkan bahwa teknologi berbasis augmented reality, virtual reality, Internet of Things (IoT), dan ICT (Information and Communication Technology) digunakan dalam meningkatkan pemahaman dan keterlibatan peserta didik pada isu-isu lingkungan di sekitarnya. Namun, beberapa tantangan dalam penerapan teknologi ditemukan, seperti infrastruktur teknologi belum merata, kurangnya pelatihan sumber daya, serta biaya implementasi yang tinggi. Studi ini dapat berfungsi sebagai titik rujukan bagi upaya penelitian masa depan yang bertujuan mengatasi hambatan dan memfasilitasi integrasi pendidikan lingkungan yang lebih produktif di seluruh konteks pendidikan. Kata Kunci: pembangunan berkelanjutan; pendidikan lingkungan; tantangan implementasi; teknologi digital